Black tongue - Shah, Binay Kumar (Journal of Advances in Internal Medicine, 2014)
No Abstract Available DOI: http://dx.doi.org/10.3126/jaim.v3i1.10699 Journal of Advances in Internal Medicine 2014;03(01):27